2021
DOI: 10.3390/covid1010032
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Functions of Protein Domains during COVID Infection: An Analysis and a Review

Abstract: Coronaviruses (CoVs) are a large viral family that can evolve rapidly emerging new strains that cause outbreaks and life-loss, including SARS-CoV, MERS-CoV, and SARS-CoV-2 (COVID-19). CoVs encode a diverse number of proteins, ranging from 5 proteins in bat CoV, to 14 in SARS CoV, which could have implication on viral tropism and pathogenicity. Here, we highlight the functional protein motifs (domains) that could contribute in the coronavirus infection and severity, including SARS-CoV-2. For this role, we used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For example, HIV-1 imitates microtubular end-binding protein 1 (EB1), disrupting cognition directly ( Naghavi, 2021 ). Other viruses, including Influenza A and Zika, exploit the host microtubular network, while SARS-CoV-2 may accomplish the same via a tubulin-like MREL motif located in the NSP1 protein ( Simpson and Yamauchi, 2020 ; Sobhy, 2021 ).…”
Section: Cell-cell Fusion In Neuropsychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HIV-1 imitates microtubular end-binding protein 1 (EB1), disrupting cognition directly ( Naghavi, 2021 ). Other viruses, including Influenza A and Zika, exploit the host microtubular network, while SARS-CoV-2 may accomplish the same via a tubulin-like MREL motif located in the NSP1 protein ( Simpson and Yamauchi, 2020 ; Sobhy, 2021 ).…”
Section: Cell-cell Fusion In Neuropsychiatric Disordersmentioning
confidence: 99%
“…The SARS-CoV-2 S protein was demonstrated to activate HERV-W-ENV gene in T lymphocytes, a protein associated with Alzheimer’s disease ( Balestrieri et al., 2021 ; Licastro and Porcellini, 2021 ). Another case of molecular mimicry was found between the SARS-CoV-2 NSP-1 antigen and host tubulin, likely connecting this virus to dysfunctional information processing ( Sobhy, 2021 ).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%
“…Those highest mutations did not occur in the functional domain. 14,15 So, the purpose of this study is to look for other nonsynonymous mutations, which were found in Indonesia samples that occur in the functional domains of ORF3a SARS-CoV-2. Furthermore, we analyze the unique truncated protein of ORF3a SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%